Pengaruh Pembelajaran Berdiferensiasi terhadap Hasil Belajar IPA Siswa Kelas VIII di SMP Negeri 5 Mataram - Ahmad Fauzan Pratama; Siti Rahmawati; Dimas Arya Nugrah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the effect of differentiated learning on the Natural Science (IPA) learning outcomes of eighth-grade students at SMP Negeri 5 Mataram. The research background stems from the limited diversity of instructional strategies capable of accommodating differences in students' learning readiness, interests, and learning profiles. This study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 64 students divided into an experimental class and a control class, selected using the cluster random sampling technique. Learning outcome data were obtained through an objective test that had met the validity and reliability requirements. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, and independent sample t-tests at a 5% significance level. The results showed a significant difference between the science learning outcomes of students who received differentiated learning and those who received conventional learning. The average learning outcome score in the experimental class was higher than in the control class, indicating that the implementation of differentiated learning had a positive effect on improving student learning outcomes. These findings suggest that adjusting instructional strategies based on students' needs, readiness, and characteristics can enhance learning engagement and optimize students' understanding of science concepts. Therefore, differentiated learning can be considered an effective alternative instructional strategy for improving the quality of the learning process and outcomes in science education at the junior high school level.